Molecular docking of citrus flavonoids with some targets related to diabetes - Shen, Wei; Lu, Yan-Hua (Bangladesh Journal of Pharmacology, 2013)
Citrus flavonoids isolated from citrus peel (flavedo and albedo) were taken as ligands for molecular docking. The molecular targets, (i.e. glucokinase, glycogen synthase kinases 3?, peroxisome proliferator-activated receptor gamma, and dipeptidyl peptidase IV) whose crystallographic structures are available on the PDB database as 1V4S, 1Q4L, 2PRG, 2ONC respectively, were used for the docking analysis using the Autodock tool V 4.2 and ADT v1.5.4 programs. The docking studies of the ligands citrus flavonoids with four different target proteins showed that citrus flavonoids are good molecules which dock well with various targets related to diabetes mellitus. The above results demonstrate that citrus flavonoids might be potentially used for blood glucose regulation.